2018
DOI: 10.1103/physrevb.97.201117
|View full text |Cite
|
Sign up to set email alerts
|

Extracting the quantum metric tensor through periodic driving

Abstract: We propose a generic protocol to experimentally measure the quantum metric tensor, a fundamental geometric property of quantum states. Our method is based on the observation that the excitation rate of a quantum state directly relates to components of the quantum metric upon applying a proper time-periodic modulation. We discuss the applicability of this scheme to generic two-level systems, where the Hamiltonian's parameters can be externally tuned, and also to the context of Bloch bands associated with lattic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 80 publications
2
115
0
Order By: Relevance
“…when q 2 y + q 2 z = ρ 2 . Consequently, performing a quantummetric tomography in the projected parameter spacefor instance, by measuring dissipative responses upon parametric modulations [45] -would offer a direct signature of the topological nodal ring. As a technical remark, we point out that such quantum-geometric measurements rely on preparing the system in a gapped state, i.e.…”
Section: < L a T E X I T S H A 1 _ B A S E 6 4 = " 2 + A R Q Y P Z 9 mentioning
confidence: 99%
“…when q 2 y + q 2 z = ρ 2 . Consequently, performing a quantummetric tomography in the projected parameter spacefor instance, by measuring dissipative responses upon parametric modulations [45] -would offer a direct signature of the topological nodal ring. As a technical remark, we point out that such quantum-geometric measurements rely on preparing the system in a gapped state, i.e.…”
Section: < L a T E X I T S H A 1 _ B A S E 6 4 = " 2 + A R Q Y P Z 9 mentioning
confidence: 99%
“…Recently, it was shown that the quantum metric is closely related to the quantum phase transition [26], superfluidity in flat bands [27], and topological matter [28][29][30]. Several schemes have been proposed to extract the quantum metric [25,[31][32][33][34][35][36], but its direct experimental measurement remains elusive. Moreover, to the best of our knowledge, a topological phase transition characterized by the ECN [24], which can be obtained from the quantum-metric measurements, is still lacking in experiments.…”
mentioning
confidence: 99%
“…The second method is to detect the excitation rate under weak periodic driving on a quantum state, as proposed in Ref. [32]. Furthermore, based on quantum-metric and Berrycurvature measurements, we explore a phase transition in a simulated time-reversal-symmetric (TRS) system, which is characterized by the ECN instead of the (vanishing) Chern number.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous proposals for extracting the quantum metric have been presented (see Refs. [21][22][23][24][25][26][27] ). The first successful measurement of the quantum metric and, actually, the full quantum geometric tensor, whose real part is the quantum metric and whose imaginary part is the Berry curvature, was performed using nitrogen vacancy centers in diamond, see Ref.…”
Section: Introductionmentioning
confidence: 99%